2015
DOI: 10.4238/2015.november.24.16
|View full text |Cite
|
Sign up to set email alerts
|

Indirect selection of industrial tomato genotypes rich in zingiberene and resistant to Tuta absoluta Meyrick

Abstract: ABSTRACT. Obtaining tomato cultivars resistant to pests through interspecific crosses between commercial cultivars and wild accessions is an important tool in integrated pest management. The aim of this study was to select tomato genotypes with high zingiberene (ZGB) levels that are resistant to the South American tomato moth (Tuta absoluta Meyrick) and to estimate genetic parameters of ZGB inheritance from the interspecific cross Solanum lycopersicum cultivar 'Redenção' x Solanum habrochaites var. hirsutum (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…Resistance caused by zingiberene and type IV and type VI glandular trichomes, both via antixenosis and antibiosis has also been reported for other important pests of the tomato crop, such as tomato pinworm Tuta absoluta (Oliveira et al, 2012), the whitefly Bemisia tabaci (Silva et al, 2009), the two-spotted spider mite Tetranychus urticae (Gonçalves et al, 2006), among others. Lima et al (2015) found high estimates of heritability for the content of zingiberene in the leaves and found the level of this allelochemical is controlled by two genes with incomplete dominance in the sense of lower content, using populations from the crossing of the Redenção variety with accession 'PI-127826'. This may reflect satisfactory genetic gains over the backcrossing over generations, using the indirect selection for resistance to arthropods pest based on zingiberene contents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance caused by zingiberene and type IV and type VI glandular trichomes, both via antixenosis and antibiosis has also been reported for other important pests of the tomato crop, such as tomato pinworm Tuta absoluta (Oliveira et al, 2012), the whitefly Bemisia tabaci (Silva et al, 2009), the two-spotted spider mite Tetranychus urticae (Gonçalves et al, 2006), among others. Lima et al (2015) found high estimates of heritability for the content of zingiberene in the leaves and found the level of this allelochemical is controlled by two genes with incomplete dominance in the sense of lower content, using populations from the crossing of the Redenção variety with accession 'PI-127826'. This may reflect satisfactory genetic gains over the backcrossing over generations, using the indirect selection for resistance to arthropods pest based on zingiberene contents.…”
Section: Discussionmentioning
confidence: 99%
“…In the population F 2 , (Lima et al 2015) selected plants with high contents of zingiberene in the leaves, which were used as a source of pollen for crossing with the Redenção variety and obtaining the generation F 1 from the first backcrossing. From self-fertilization of plants F 1 RC 1 , we obtained the segregating population (F 2 ) of the first backcrossing for the Redenção variety used in the present study.…”
Section: Acquisition Of Genotypes With High Zingiberene Content and Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this, a rapid, low-cost spectrophotometric methodology was established for ZGB quantification in tomato leaves [81]. This method is now routinely applied in tomato breeding programs regarding pest insects and arachnids [22,26,82,83].…”
Section: Allelochemical Quantification Techniquesmentioning
confidence: 99%
“…When investigating ZGB content inheritance in the interspecific intersection between S. lycopersicum and S. habrochaites var. hirsutum accession 'PI-127826', it was observed that leaf ZGB content is controlled by two genes with incomplete dominance in the sense of lower content, presenting greater heritability in the broad sense (81.9%) [26]. When evaluating the synergistic effect between high AA and ZGB leaf content, heterozygous genotypes were used for both characters [6], and the authors observed that the fact that heterozygous double genotypes show the same behavior as the heterozygotes only for ZGB or AA indicates that, although allelochemicals act similarly on the resistance of these genotypes to whitefly, they do not present a synergistic effect in this case.…”
Section: Zingiberene Resistance Introgressionmentioning
confidence: 99%